The Effectiveness of Village-Based Foreigner Supervision at the Class I Special TPI Ngurah Rai Immigration Office - Reni Desnita Purba; Cokorde Istri Dian Laksmi Dewi; Putu Eka Trisna Dewi (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
The Ngurah Rai Immigration Office on November 4, 2022 launched the policy of Integration of Supervision and Services for Foreign Citizens Based on Villages (I Wayan Wisesa). This policy is a strategic step to increase community participation in supervising the presence and activities of foreigners. This policy embraces the Head of the Environment, however, in 2 years of its implementation, this policy has not been effective as indicated by the low number of complaints. This preventive effort has not been able to stem the rampant viral news of naughty behavior by foreign tourists in Bali. Normative Juridical Research with a sociological juridical approach resulted in the following conclusions: a) The ineffectiveness of the implementation of I Wayan Wisesa is due to the very high acceptance of Balinese people towards foreign tourists; a strong stigma in society that monitoring the presence and activities of foreigners is the responsibility of Immigration officers; and Security officers in the village environment do not yet have adequate competence, sectoral egos, lack of socialization, and low legal awareness of the Community; b) Strategic steps that can be taken are as follows: improving the quality of cross-agency coordination; increasing the intensity and effectiveness of socialization and education on the importance of supervising foreigners; allocate a budget for supervision for Community and Head of Environment involvement; Wayan Wisesa's workflow needs to be arranged.